Development Of Interactive Media Based On Quizzizz Paper Mode Science Education As An Effort To Improve The Character Profile Of Pancasila Students - Syarifah Zahara; Ayu Rahmi; Sirry Alvina; Intan Ananda; Nurfadilah Nurfadilah (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The digital era is one of the fields that influences the civilization of the 5.0 revolution on world mobility. Learning media as a tool that helps the learning process in presenting material in an interesting way so that the learning situation becomes effective, efficient, active and easy to understand by students. One of the innovations of learning media in the digital era is learning media based on Quizizz Paper - Mode which is a means to facilitate teachers in developing innovative media and for planning interesting learning and can accompany students in the learning process. The purpose of this study was to determine how the validity (by academic media and material experts), feasibility (by media and material expert teachers), and student responses through the implementation of interactive media design based on Quizizz Paper - Mode as an effort to create learning innovations in improving the character of Pancasila student profiles for students of SMAN 2 Biruen. The development of learning media based on Quizizz Paper - Mode Science education uses research and development methods . This study uses the ADDIE development model which is developed consisting of five stages: Analysis , Design , Development , Implementation and Evaluation . Data collection techniques and instruments with validation tests, feasibility tests, student responses through questionnaires. The results of the validity test from media experts obtained results of 85% with the category "Valid", and material experts 75% with the category "Valid". Based on the results of the feasibility test with teachers of SMAN 2 Bireun, the results were 87.50% with the category of feasible and the results of the student response assessment obtained a score of 87.30% with the category of interesting. For N-Gain percent, the average value obtained was 76.2407. This value is greater than 76.00. So it can be concluded that the questions given to students through quizzis paper mode can improve the character of Pancasila profile students. The design of the quizizz paper mode media and the questions chosen are very interesting in science education which aims to strengthen student character in the Pancasila student profile program.